Electron energization during merging of self-magnetized, high-beta, laser-produced plasmas. (5th August 2021) - Fiksel, G.; Fox, W.; Rosenberg, M.J.; Schaeffer, D.B.; Matteucci, J.; Bhattacharjee, A.
Abstract : Electron energization during merging of magnetized plasmas is studied using the OMEGA and OMEGA EP laser facilities by colliding two plasma plumes, each containing a Biermann-battery self-generated magnetic field. Two neighbouring plasma plumes are produced by intense laser beams, and the anti-parallel Biermann fields merge and reconnect in the process of the plumes' expansion and collision. To isolate the merging as an acceleration source, the electron energy spectra obtained from two-plume collision shots are compared with the spectra from single-plume shots. Single-plume shots exhibit an energized electron tail with energies up to ${\sim }250\ keV$ . The electrons in merging experiments are additionally accelerated by ${\sim }50\text {--}100$ keV compared to single-plume shots.